Âdâbu Al-Muta’allim ‘Inda Al-Imâm Al-Bukhârî Fî Kitâ Bihi Al-Adabu Al-Mufrad - Aprianto, Adi; Alim, Akhmad; Supraha, Wido (Tawazun: Jurnal Pendidikan Islam, 2020)
Islam is a religion of adab and ethics, and Islamic Sharia is very noticing. But in fact, there are still many students who commit the offence that is contrary to Islamic etiquettes, such as examples brawl. This background is the impetus for the writer to dig deeper into the concept of the Adab of the student in the Adabul Mufrod Imam al-Bukhaari. This research is a study of literature with a content-analytic approach. The research has produced ethics learners, including those related to ethics with God, such as the obligation of sincerity. Some that relate to morals with parents, such as providing parents to others, some of which are related morals, respect colleagues sitting. These last public morals must concerned learner avoiding dishonourable. Abstrak Islam adalah agama yang menjunjung tinggi adab dan etika yang baik. Akan tetapi pada kenyataannya masih banyak pelajar muslim yang melakukan pelanggaran yang bertentangan dengan adab islami, seperti contoh tawuran antar sekolah, pergaulan bebas dan lainnya. Hal inilah yang menjadi dorongan bagi penulis untuk menggali lebih dalam konsep adab pelajar dalam kitab Adabul Mufrod karya Imam Bukhori. Penelitian ini merupakan studi literatur dengan pendekatan conten analysis. Penelitian ini menghasilkan bahwa adab peserta didik mencakup adab kepada Allah, seperti kewajiban ikhlas dalam belajar, adab kepada orang tua, seperti memprioritaskan orang tua dari yang lainnya, adab terhadap sesama pelajar, seperti rasa hormat terhadap rekan satu majlis, dan terakhir adab yang harus diperhatikan secara umum seperti menjauhi segala sesuatu yang membuat wibawanya jatuh.